Analisis Pengatalogan Deskriptif di Perpustakaan Madrasah Aliyah Swasta (MAS) PP Jabal Rahmah Koto Baru Sungai Tarab Ditinjau dari Standar AACR 2 - Yola Febrianti (Jurnal Ilmu Perpustakaan dan Informasi Islam, 2022)
Abstract : The emphasis of this research is on the standard of descriptive cataloging of library materials as seen from the AACR 2 guidelines at the Jabal Rahmah Koto Baru MAS Library, Sungai Tarab. This study aims to describe descriptive cataloging standards of a collection, describe the use of catalogs as a means of information retrieval, and describe the obstacles faced in cataloging activities at the MAS Jabal Rahmah Koto Baru library, Sungai Tarab. The research method used is descriptive with a qualitative approach. Data collection techniques by observation, interviews, and documentation. The data analysis technique in this study starts from data reduction, data presentation and conclusion drawing. The validity of the data in this study used data triangulation, source triangulation and technical triangulation. The result of this research is that the library of MAS Jabal Rahmah Koto Baru Sungai Tarab has not followed the AACR standards that have been set. The use of catalogs by users at the Jabal Rahmah MAS library has not been utilized. The obstacles faced by the library are the lack of personnel (HR) and lack of understanding of librarians regarding cataloging and other processing, as well as insufficient library space or not following the standards of the school library room.Keywords: Cataloging Standards, MAS Jabal Rahmah Library, Catalog Utilization